2000
DOI: 10.1111/j.1349-7006.2000.tb00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Susceptibility of Long‐Evans Cinnamon Rats to N‐Butyl‐N‐(4‐hydroxybutyl)‐nitrosamine‐induced Urinary Bladder Carcinogenesis and Inhibitory Effect of Urinary Copper

Abstract: We studied the susceptibilities to N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN)-induced urinary bladder carcinogenesis of male Long-Evans Cinnamon (LEC), F344 and Long-Evans Agouti (LEA) rats. Male rats (n = = = =21) were given 0.1% BBN in their drinking water from week 6, 8 and 10 for one week, and killed in week 56. The incidences of transitional cell tumors (papillomas plus carcinomas) in BBN-treated LEC and F344 rats were 12% and 76%, respectively (P < < < <0.001, experiment 1), and those in LEC and LEA rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In a recent carcinogenicity study, we found that LEC rats were more resistant to BBN-induced bladder carcinogenesis than F344 or Long-Evans Agouti rats. 24) Therefore, LEC rats are not necessarily a carcinogen-susceptible strain. In the present study, LEC rats were resistant to DEN-induced lung carcinogenesis, and WKAH.C-Atp7b and WKAH rats were susceptible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent carcinogenicity study, we found that LEC rats were more resistant to BBN-induced bladder carcinogenesis than F344 or Long-Evans Agouti rats. 24) Therefore, LEC rats are not necessarily a carcinogen-susceptible strain. In the present study, LEC rats were resistant to DEN-induced lung carcinogenesis, and WKAH.C-Atp7b and WKAH rats were susceptible.…”
Section: Discussionmentioning
confidence: 99%
“…24) Therefore, LEC rats are not necessarily a carcinogen-susceptible strain. In the present study, LEC rats were resistant to DEN-induced lung carcinogenesis, and WKAH.C-Atp7b and WKAH rats were susceptible.…”
Section: Discussionmentioning
confidence: 99%
“…our studies (6,7). Prenatal and neonatal administrations of N -ethyl-N -nitrosourea (ENU) induce brain and trigeminal nerve tumors (8).…”
Section: Low Susceptibility To N -Ethyl-n -Nitrosourea-induced Transpmentioning
confidence: 98%
“…The difference in hepatocarcinogenic activity may not be explained with reference to metabolic potential, since there are no apparent differences in the urinary excretion of BCPN among the 4 rat strains (Wistar, ACI/N, SD and NAR) 23 . It was earlier reported that Long-Evans Cinnamon (LEC) rats, when compared to F344 rats, showed high susceptibility to liver carcinogenesis initiated/induced by BBN, related to marked liver lesions which occur because of a genetical alteration 24 . We have described lack of variation in susceptibility of F344 and WS (a Wistar-derived strain) rats to BBN-induced liver carcinogenesis 10 , in line with the finding that F344 and Wistar rats exhibit the same degree of susceptibility to initiation by diethylnitrosamine 25 .…”
Section: Discussionmentioning
confidence: 99%